Face Liveness Detection: A Comprehensive Study on Techniques and Applications - Suman, Saurabh; Salimath, Nagesh (Journal of Neonatal Surgery, 2025)
Face liveness detection is crucial for preventing spoofing attacks on authentication systems. This paper presents a deep learning-based approach for face liveness detection, utilizing convolutional neural networks (CNNs) and recurrent neural networks (RNNs). This paper presents a comprehensive study of face liveness detection, an essential task for preventing spoofing attacks in facial recognition systems. The paper reviews various techniques, from traditional handcrafted methods to modern deep learning approaches, and evaluates their effectiveness in real-world scenarios. A comparative analysis of algorithms and datasets used in the field is also conducted. The study further discusses the challenges, limitations, and future directions for improving face liveness detection systems.